Novel organization of mitochondrial minicircles and guide RNAs in the zoonotic pathogen Trypanosoma lewisi - Li, Su-Jin; Zhang, Xuan; Lukeš, Julius; Li, Bi-Qi; Wang, Ju-Feng; Qu, Liang-Hu; Hide, Geoff; Lai, De-Hua; Lun, Zhao-Rong (Nucleic acids research, 2020)
Kinetoplastid flagellates are known for several unusual features, one of which is their complex mitochondrial genome, known as kinetoplast (k) DNA, composed of mutually catenated maxi- and minicircles. Trypanosoma lewisi is a member of the Stercorarian group of trypanosomes which is, based on human infections and experimental data, now considered a zoonotic pathogen. By assembling a total of 58 minicircle classes, which fall into two distinct categories, we describe a novel type of kDNA organization in T. lewisi. RNA-seq approaches allowed us to map the details of uridine insertion and deletion editing events upon the kDNA transcriptome. Moreover, sequencing of small RNA molecules enabled the identification of 169 unique guide (g) RNA genes, with two differently organized minicircle categories both encoding essential gRNAs. The unprecedented organization of minicircles and gRNAs in T. lewisi broadens our knowledge of the structure and expression of the mitochondrial genomes of these human and animal pathogens. Finally, a scenario describing the evolution of minicircles is presented.
Keywords: Mitochondria; Phylogeny; genom mitochondriální; adenosintrifosfatasy; podjednotky proteinů; RNA, Protozoan; Genome, Mitochondrial; protozoální DNA; Trypanosoma lewisi; DNA, Protozoan; mitochondrie; Adenosine Triphosphatases; editace RNA; RNA Editing; guide RNA, Kinetoplastida; fylogeneze; RNA protozoální; Protein Subunits; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; RNA, Guide, Kinetoplastida